The Analysis Study of Association of Type 2 Diabetes Mellitus and Hepatocellular Carcinoma : A Comprehensive Systematic Review - Muhammad Ilham Wira Tri Putra; Asra Dewita Namora Harahap (The Indonesian Journal of General Medicine, 2024)
Background: Hepatocellular carcinoma (HCC) is the most prevalent form of liver cancer, and its incidence and mortality have been steadily increasing in recent decades. Numerous studies have shown that individuals with type 2 diabetes are more likely to develop HCC. This systematic review aims to evaluate the association regarding the role of diabetes in the development and progression of HCC based on literatures of the last decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: T2DM is a significant risk factor for HCC, especially with metabolic comorbidities. GLP-1RAs show promise in reducing this risk. Public health interventions are needed to improve diabetes management, and further research is essential to validate and explore these findings.